Development of Guided Inquiry Learning E-Module Assisted by Virtual Lab on Material of Straight Motion Dynamics - Elsa Farida; Z Zulirfan; Syahril Syahril (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2022)
Learning is still centered on the teacher with the habit of the lecture method and students only accept what the teacher says so that students do not absorb the full learning. To overcome this, student-centered learning is needed which can be overcome by using learning media, one of which is e-modules. The purpose of this research was to produce an e-module of guided inquiry learning assisted by a virtual lab on valid and practical straight motion dynamics material. This type of research uses research and development (R&D) with the ADDIE development model which is limited to practicality at the development step. The developed e-module is divided into 3 meetings. Data were collected through a validation assessment sheet consisting of material, media, and pedagogic aspects which were validated by 3 experts. In addition, e-module practicality data consisting of ease of use, efficiency, language, and benefits use a practicality assessment sheet. The data obtained were analyzed descriptively. The validation results show that the e-module obtained an average of 3.63 with a valid category, while the results of the practicality test by the teacher's response got an average of 3.73 in the very high category and the average student response results in 3.66 in the very high category. It can be concluded that the guided inquiry learning e-module assisted by a virtual lab on linear motion dynamics material is valid and practical, so it is expected to help high school students in learning physics.